Peculiar features of intravenous immunoglobulins application in rheumatic diseases - O. N. Egorova; G. M. Tarasova; A. V. Datsina; E. G. Sazhina (Современная ревматология, 2024)
Intravenous immunoglobulins (IVIG) are the most commonly used immunobiological agents produced from donor blood. They were first used in the mid-twentieth century for the treatment of primary immunodeficiencies. Later, they were successfully used to treat a variety of autoimmune, inflammatory and other diseases. There are currently a growing number of basic and clinical studies looking at the mechanism of action and efficacy of different doses of IVIG. At the same time, much remains unclear, contradictory, and some data are mutually exclusive.